A study on micronuclei in tobacco and related habits - Twinkal S Patel; Anjani R Chaudhary; Bhavin B Dudhia; Parul V Bhatia; Purv S Patel; Yesha V Jani (Wolters Kluwer Medknow Publications, 2021)
Introduction: Oral cancer is one of the ten most common causes of mortality in developing countries like India. A micronucleus (MN) is a small extra nucleus separated from the main one, generated during cellular division by late chromosomes or by chromosome fragments. Micronucleus is a potential biomarker for malignancy. Aim and Objectives: The study attempts to analyze micronuclei in buccal smear from patients with tobacco and related habits; and to determine its reliability as a biomarker for carcinogenesis. Study Design: A total of 400 consisting of normal subjects, patients with potentially malignant lesions and patients with malignant lesions were included in the study. Oral exfoliated cells were collected by scrapings of buccal mucosa of both control and study groups with a tooth brush. The scrapings collected from right and left buccal mucosa of each subject were studied under two separate slides. A total of 500 cells were examined from each slide. All the micronucleus cells located on each slide were examined again under the 100X magnification. Results: The P value for intergroup difference in average number of micronuclei in cells of buccal mucosa among all groups was <0.001 which was highly significant. The P value for micronucleated cells of buccal mucosa among all groups was <0.001 which was highly significant. Conclusion: A stepwise increase in MN counts from normal to potentially malignant to carcinoma suggested a link of this biomarker with neoplastic progression. Micronuclei can be used as a biomarker for early detection of premalignant and malignant lesions of the oral cavity.